ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS X SMAN 1 SINDUE TOBATA PADA MATERI TRIGONOMETRI DITINJAU DARI GAYA BELAJAR - Anifan, Anifan; Murdiana, I Nyoman; Karniman, Tegoeh S. (Universitas Tadulako, 2023)
This study aims to obtain a description of the mathematical understanding abilities of class X students of SMAN 1 Sindue Tobata on trigonometry based on learning styles. This type of research is descriptive with a qualitative approach. The subjects of this study were three students of class X MIPA 1 who had visual, auditory, and kinesthetic learning styles. Data were collected through written assignments and interviews. Based on the indicators of students' mathematical understanding ability, the research results obtained were (1) subjects with a visual learning style type were able to restate the trigonometry concepts they had learned, were not able to present trigonometry concepts in various forms of mathematical representations and were not able to use, utilize, and choose procedures or trigonometry calculation operations in completing tasks correctly. (2) subjects with the type of auditory learning style can restate the trigonometry concepts that have been learned, have not been able to present trigonometry concepts in various forms of mathematical representations, and can’t determine the trigonometry ratio formula correctly. (3) subjects with a type of kinesthetic learning style, namely being able to restate the trigonometry concepts that have been learned, not being able to present trigonometry concepts in various forms of mathematical representations, not being able to use, utilize, and choose procedures or arithmetical trigonometry operations correctly.